Comparative study of anti-vertiginous and anti-anxious drugs for the treatment of chronic vestibular patients with secondary anxiety. (3rd July 2019) - Sato, Go; Matsuda, Kazunori; Matsuoka, Momoyo; Fukuda, Junya; Morita, Yuka; Takahashi, Kuniyuki; Horii, Arata; Takeda, Noriaki
Abstract: Background: Regarding the relationship between psychiatric disorders and dizziness, anxiety is the most frequently seen psychiatric disorder in dizzy patients. Objective: We compared the effects of anti-anxious benzodiazepines (loflazepate) and anti-vertiginous cholinergic antagonist (diphenidol) on the subjective symptoms in chronic vestibular patients with secondary anxiety. Methods: Forty-three patients who had chronic dizziness lasting more than three months due to organic vestibular diseases with secondary anxiety. Anxiety was evaluated by the State-Trait Anxiety Inventory (STAI). Subjective handicaps due to dizziness were assessed by the validated questionnaire consisted of 14 questions that were categorized into two physical and three emotional factors. During the initial six months of the study, 21 patients were treated by anti-anxious benzodiazepines (loflazepate, 2 mg/day) for four weeks, whereas anti-vertiginous cholinergic antagonist (diphenidol, 75 mg/day) was used for four weeks for other 22 patients during the later six months-period. Subjective handicaps and STAI were compared between pre- and post-treatment. Results: Loflazepate improved not only three emotional factors and state anxiety but also one of the physical factors. Diphenidol improved two physical factors but no emotional factors nor state and trait anxiety. Conclusions: Targeting for comorbid anxiety was beneficial for subjective symptoms of chronic dizziness with secondary anxiety.